Negative emotions associated with self-growth among older adults during the COVID-19 pandemic. (1st June 2022) - Von Humboldt, S.; Mendoza-Ruvalcaba, N.M.; Arias-Merino, E.D.; Ribeiro-Gonçalves, J.A.; Cabras, E.; Low, G.; Leal, I.
Abstract : Introduction: The Covid-19 pandemic appeared globally (1), thus affecting the self-growth of the older population (2). Objectives: The aim of this study is to identify and analyze the negative emotions felt during the pandemic, as well as their impact on self-growth of 226 older individuals of four nationalities: Mexican, Italian, Portuguese and Spanish. Methods: Thus, a transnational qualitative survey was carried out. A content analysis was performed. Results: Seven negative emotions were reported, namely: fear, sadness, anger, grief, annoyance, loneliness and shame. These emotions were considerably associated with the following themes: (1) Sharing experiences; (2) Availability of the partner; (3) Spirituality and religion; (4) Be active; (5) Interest in new projects; (6) Civic participation; (7) Sexual activity. Older participants with Mexican and Italian nationality reported that sharing experiences as the most relevant topic, while for the Portuguese and Spanish participants, having a partner available was more important. Conclusions: This study demonstrated that negative emotions cooperated with the self-growth of older individuals during the Covid-19 pandemic. The heterogeneity of experiences lived by each culture was highlighted, underlining the positive side of negative emotions and their strong connection with the self-growth of the older people. 1.von Humboldt S et al. Smart technology and the meaning in life of older adults during the Covid-19 public health emergency period: A cross-cultural qualitative study. Int Rev Psychiatry, 2020; 1-10. 2. von Humboldt S et al. Does spirituality really matter? - A study on the potential of spirituality to older adult's adjustment to aging. Jpn Psychol Res, 56; 114-125. Disclosure: No significant relationships.